Bio-inspired, colorful, flexible, defrostable light-scattering hybrid films for the effective distribution of LED light. Issue 26 (26th June 2017) - An, Seongpil; Jo, Hong Seok; Kim, Yong Il; Song, Kyo Yong; Kim, Min-Woo; Lee, Kyu Bum; Yarin, Alexander L.; Yoon, Sam S.
Abstract : A transparent, colorful, flexible, defrostable light-scattering hybrid film. Abstract : Bioluminescent jellyfish has a unique structure derived from fiber/polymer interfaces that is advantageous for effective light scattering in the dark, deep sea water. Herein, we demonstrate the fabrication of bio-inspired hybrid films by mimicry of the jellyfish's structure, leading to excellent light-scattering performance and defrosting capability. A haze value reaching 59.3% and a heating temperature of up to 292 °C were achieved with the films. Accordingly, the developed surface constitutes an attractive optical device for lighting applications, especially for street or vehicle luminaries for freezing Arctic-climate countries. The morphological details of the hybrid films were revealed by scanning electron microscopy. The light-scattering properties of these films were examined by ultraviolet-visible-infrared spectrophotometry and anti-glare effect analyses. The defrosting performance of the hybrid films was evaluated via heating tests and infra-red observations.